2022
DOI: 10.1186/s12902-022-01023-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of MC4R rs17782313 variants and dietary carbohydrate quantity and quality on basal metabolic rate and general and central obesity in overweight/obese women: a cross-sectional study

Abstract: Background Recent studies have shown that dietary carbohydrate quantity and quality as well as genetic variants may contribute to determining the metabolic rate and general and central obesity. This study aimed to examine interactions between melanocortin 4 receptor gene (MC4R) rs17782313 and dietary carbohydrate intake, glycemic index (GI), and glycemic load (GL) on body mass index (BMI), waist circumferences (WC), basal metabolic rate (BMR), and BMR/kg in overweight/obese women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…These might indicate that different types of obesity have different mechanisms. Higher carbohydrate intake is related to an increase in BMR/kg in women with overweight or obesity [ 41 ]. This coincides with our study in that “obese people eat more carbohydrates that did not suffer from muscle loss, while people with sarcopenia and sarcopenic obesity intake less carbohydrates intake”.…”
Section: Discussionmentioning
confidence: 99%
“…These might indicate that different types of obesity have different mechanisms. Higher carbohydrate intake is related to an increase in BMR/kg in women with overweight or obesity [ 41 ]. This coincides with our study in that “obese people eat more carbohydrates that did not suffer from muscle loss, while people with sarcopenia and sarcopenic obesity intake less carbohydrates intake”.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been identified as a risk factor for obesity in offspring [21][22][23][24][25]. Other SNPs, such as rs17773430, have been associated with a higher percentage of fat mass [26][27][28], and rs34114122 is associated with an increase in plasma ghrelin levels and energy intake [29]. However, with advances in the understanding of the role of the MC4R gene, some points remain to be clarified, such as the effect of polymorphism combinations on the gene.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most studies in this area of research have been conducted in Western countries where red meat consumption has been reported to be high, while people living in the Middle East, have a special pattern of consumption. Iranian people consume a large amount of carbohydrates in their usual diets [ 19 ] and have a higher intake of full-fat red meats, compared to other meats [ 8 ]. Moreover, the intake of fish per capita in Iran is lower than the international standard [ 20 ].…”
Section: Introductionmentioning
confidence: 99%